Meta-Analysis: The Influence of Knowledge, Education, and Husband's Support on The Selection of Long Acting Contraception Methods - Nurul Aulia Rahmi; Izaak Zoelkarnain Akbar; Bahrul Ilmi; Meitria Syahadatina Noor; Rosihan Adhani (Jurnal Berkala Kesehatan, 2021)
The population is expected to increase by 8,5 billion persons in 2030 and 10,9 billion persons in 2100, population is growing at a rate of around 1,1% per year.  One of population growth control by birth control with contraception. The most effective contraception is long-acting contraception, however, on IDHS (Indonesian Health Demographic Survey) only 13% of currently married women use long-acting contraception. Many factors affect contraceptive use among married women, such as knowledge, education, and husband’s support. The purpose of this study was to determine the effect of knowledge, education, and husband's support on the selection of MKJP. This study used meta-analysis with the search engines by Google scholar, PUBMED, science direct, and ProQuest. The study was selected using PRISMA and it was evaluated by AMSTAR. Data synthesis was conducted by STATA 16.0. The results of this study obtained by knowledge [OR = 0,99; 95% Cl : 0,90-1,08, p = 0,000; I2 = 74,8%], education [OR = 0,84; 95% Cl : 0,77-0,92, p = 0,000; I2 = 86,3%], and husband’s [OR = 0,94; 95% Cl : 0,69-1,20, p = 0,000; I2 = 81,5%]. This means that knowledge, education, and husband’s support have an impact on the use of long-acting contraception.